Low‐complexity user scheduling for MMSE relaying with large‐scale arrays. Issue 2 (1st January 2015) - Liu, Haijing; Gao, Hui; Lv, Tiejun
Abstract : An enhanced round‐robin scheduling (RRS) scheme for multi‐pair multi‐input–multi‐output relay systems is proposed, where the relay is equipped with a large‐scale antenna array and performs minimum mean‐square error (MMSE) data processing. Compared with the traditional RRS, significant sum rate performance improvement by setting the number of active user pairs to an appropriate value is achieved.